Kebijakan Pidana Dalam Pelanggaran Hak Cipta - Yoyo Arifardhani (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThe legal relationship between the creator / owner of rights Associated with copyright infringers is essentially a